Export-Led Policy, Agricultural, Industrial, and Financial Sectors Growth in Cameroon - Fondem, Divine B.; Luo, Yongli (Business and Economic Research, 2023)
<span style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">This paper investigates the relationship between export and sectoral growth in Cameroon. The study retrieves time series data from the World Bank database during 1970-2021 . It applies the unit roots test, the Johansen cointegration test, and vector error correction model to investigate the long-run relationship between export expansion and sectoral growth. The results indicate that the long-run relationship exists between export and agricultural, industrial, as well as financial sectors’ growth in Cameroon. The impulse response function clearly shows that a unique shock to export would positively affect sectoral growth. In general, it suggests that the export-led policy will eventually enhance the economic growth and development in the agricultural, industrial, and financial sectors in Cameroon.